Optimización de los motores de búsqueda en el afianzamiento de marca - Salas Coz, Erwin (2024)
Introduction: During the health crisis due to the pandemic, SMEs had not developed their brand on online internet channels, and they were forced to integrate into virtual commerce. Despite the efforts made by SMEs, they have low levels of virtual digitisation in relation to large companies. This paper aims to analyse the implementation of the Internet search engine optimisation (OMB) methodology in brand consolidation. Method: A case study was developed in a small company in Lima, Peru. The research results show that the OMB promotes brand consolidation, which means that the OMB methodology can be extended to other small companies to improve their brand positioning.